DEVELOPMENT OF CROSS-CULTURAL COMMUNICATION SCALE FOR INDONESIAN CONTEXT - Harlina Harlina; Yosef Yosef; Sigit Dwi Sucipto; Ma’rifatin Indah Kholili (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
There are limited instruments to measure the cross-cultural communication, particularly in Indonesia. Therefore, this study aims to produce an instrument of competence and cross-cultural communication that valid and reliable. We used research and development methods to achieve the aims. The results of three experts, namely readability experts, material experts and linguists on average the results of the validator obtained a score of 20 and were categorized as good. From the results of the three validators used as input to improve the instrument after being revised the instrument was tested on the research subject. The results of the trial there were 27 invalid items so the instrument test results are valid, there are 39 items are worth using. For reliability results obtained correlation coefficient 0.882 in the high category. Based on the research results, the competency and cultural cross-cultural communication instruments meet the valid and reliable criteria and are suitable for use in Indonesian context.